(3QSGdI aj GdMceIs - (3GdbhGei, GdTjQGRj, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1050(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdPj CNQL ef ecfhfGJ YfGjJg eG COQL aj Gdbde(B...(3hHYO ajbhd NGOe Gdbhi GdYbdjI hQGUO GdMbGFb GdeKHJI eMeO GdTgjQ HUOQ GdTjQGRj(B...(3aj HjGf GdYfGjI GdEdGgjI heYfi GdbVGA hGdbOQ(B...s
(3BNQgG (B:s
...(3cd Pdc jOd Ydi Cf GdYGde cdg aj ebGe GdTghO(B...(3eNdhb dg bhI GdJacQ(B...(3aCYVGA GdHOf cdgG eSHMI fGWbI(B...(3aGdMce ddg GdYdj GdcHjQ JeJs
(3JHUQI GdeDda (B:s
(3CQN UGMH GdCYdGe dhaGJg SfI(B: 1059(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B31s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs